2018
DOI: 10.1080/13678868.2018.1468588
|View full text |Cite
|
Sign up to set email alerts
|

The capability approach and national development in Nigeria: towards a youth transition model

Abstract: This paper adapts a qualitative-dominant mixed method approach by utilizing policy documents, semi-structured interviews (SSIs), a focus group discussion, and structured questionnaires (SQs) to explore the transitio n-related bottlenecks that impede capability development processes across the education-work transition pathway, with a specific focus on the national youth service corps (NYSC) route. This paper reveals that youth's (aged 18-30) ability to navigate the formal education phase, partly depends on mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…They focused on interactions between the exosystem and ontogenic levels, with particular attention on how high unemployment among youths and young adults could be combatted through HRD, thereby meeting the overall socio‐economic goals of the country. Arubayi and Akobo (2018) gave prominence to interactions between exosystem characteristics and lower levels of the EST framework in suggesting that efforts to improve youth unemployment and equip young people with relevant skills to enter or compete in the labour market in Nigeria have been largely unsuccessful, because they did not engage with ontogenic characteristics and customize NHRD provision.…”
Section: Resultsmentioning
confidence: 99%
“…They focused on interactions between the exosystem and ontogenic levels, with particular attention on how high unemployment among youths and young adults could be combatted through HRD, thereby meeting the overall socio‐economic goals of the country. Arubayi and Akobo (2018) gave prominence to interactions between exosystem characteristics and lower levels of the EST framework in suggesting that efforts to improve youth unemployment and equip young people with relevant skills to enter or compete in the labour market in Nigeria have been largely unsuccessful, because they did not engage with ontogenic characteristics and customize NHRD provision.…”
Section: Resultsmentioning
confidence: 99%
“…The HRD community is steadily producing quality research focused on African experiences. Recent works include studies of learning transfer (Kiwanuka, Miiro, Matsiko, & Nkalubo, 2020;Suleiman, Dassanayake, & Abang Othman, 2018), teacher training (Oonyu, 2019), higher education (Johnson, 2019), skills & capabilities development (Arubayi & Akobo, 2018;Oats & Gumbo, 2019;Otchia & Yamada, 2019;Yamada, Otchia, & Taniguchi, 2018), healthcare and literacy systems (Akello, Lutwama-Rukundo, & Musiimenta, 2017;Davis, Arana, Creel et al, 2018;Davis, Menser, Juarez, Tomaszewski, & Kash, 2019;Regmi, 2019;Wekullo, Davis, Nafukho, & Kash, 2018), promoting learning (Biney, 2019), and leadership development (Modisane, 2018) post-coloniality and NHRD (Ekuma, 2019), and collaborations in North-South scientific international projects (Lutomia, 2019). While various components of program planning are discussed throughout this literature, none of the recent studies center a planning process in their research.…”
Section: Recent Hrd Literature Centering African Perspectivesmentioning
confidence: 99%
“…With studies having shown that mental health problems are more common among medical personnel [13], corps medical doctors are at risk of various psychosocial problems which may or may not be related to their profession. The lack of adequate support structure has been implicated in the poor performance of the scheme [14]. A study by O S Fadairo in 2010 concluded that the influence of the NYSC scheme on the development of youth corps members was perceived to be poor by the majority of the respondents [15].…”
Section: Introductionmentioning
confidence: 99%